Relatório de Estágio Profissional "A Vida concretiza-se com o realizar dos nossos sonhos: O Desenvolvimento do Saber através da Prática". - José Diogo Lopes Monteiro (2019)
This report refers to the Professional Internship, which is inserted into the 2nd year of Learning of the 2nd year of the Master's Degree of Physical Education Teaching in Basic Education and High School in the College of Sport of the University of Porto. This year is the culmination of the years of academic path, now being able to apply the acquired knowledge and the initial formation, pre-professional. However, this document reports all the experiences and the constant evolution over school year of the teacher in question. Being able to observe all the process applied to the class of which I was responsible for, from the planning, to the realization e consequent evaluation. It is noted that the report is divided in five chapters. The first one refers to the "Introduction", which promotes all the purpose and objetive of this document. The second one, being the "Biographical Framing", highlights and describes all the journey and the influences that originated the decision of being a teacher, all the created expectations and the value of the internship. Next, we have "Framing of the Professional Practice", describing what went on in the professional internship at a institutional level, highlighting the context of where it happened. The fourth one, "Realization of the Professional Practice", refers to the 3 areas of performance of the teacher, all the process of school anticipation, its application and consequent evaluation. The participation with the school community e lastly, the Study of Action-Research, refering to the theme "Physical Education on 21st Century, The use of cellphones as a booster of motivation for the students" which is a part of the Professional Development. The last chapter, makes the "Conclusion and Future Perspectives", it highlights the final thoughts at the end of the internship, the created perception and the desires to enter the professional life. The richness of the internship allows to portray countless experiences, developing me as a teacher. Besides that, it is a way of creating a sort of bridge between theory and practice, so it isn't a shock when I make my way into a teaching career. It is the beggining of a new path, being able to leave a mark in the teaching world.